The deformation value effect on the Ta-W-Ta solid-phase junction nature with intermediate Ti (titanium) interlayers for the neutron-producing target of the neutron source - Borts, B.V.; Zelinsky, A.Yu.; Parkhomenko, A.A.; Sytin, V.I.; Gluschenko, L.I.; Tkachenko, V.I.; Vorobyov, I.A.; Pidlisnyi, A.D.; Lopata, A.A.; Domnich, M.P.; Patochkin, I.V. (Вопросы атомной науки и техники, 2022)
The paper presents the quality studies results of the Ta-W-Ta solid phase junctions with Ti interlayers obtained by hot roll bonding in vacuum, that determine the work suitability in the form of neutron producing targets at the research nuclear facility ‘Source of Neutrons’. It is shown the layers mutual penetration level of the Ta-W-Ta solid-phase junction with Ti interlayers which provides a high level of clad layers adhesion when using the hot vacuum roll bonding method. The deformation parameters necessary both for the solid phase bond occurrence and for the reliable solid-phase junction formation of tantalum and tungsten refractory metals layers through a titanium interlayer, with a joint strength exceeding the value of a less durable material are determined. The possibility of chemical vapor deposition (CVD) method using for side faces coating of targets was studied. Представлено результати досліджень якості твердофазних з’єднань Ta-W-Ta з прошарками Ti, отриманих методом гарячої прокатки у вакуумі, що визначають придатність до роботи у вигляді нейтронно-утворюючих мішеней на дослідній ядерній установці “Джерело Нейтронів”. Показано ступінь взаємного проникнення шарів твердофазного з’єднання Ta-W-Ta з прошарками Ti, що забезпечує високий рівень адгезії плакованих шарів при використанні методу гарячої вакуумної прокатки. Визначено параметри деформації, необхідні як для виникнення твердофазного зв’язку, так і для утворення надійного твердофазного з’єднання шарів тугоплавких металів танталу та вольфраму через титановий прошарок, з міцністю з'єднання, що перевищує значення менш міцного матеріалу. Вивчено можливість використання способу хімічного газофазного осадження (ХГО) для покриття бічних граней мішеней. Представлены результаты исследований качества твердофазных соединений Ta-W-Ta с прослойками Ti, полученных методом горячей прокатки в вакууме, определяющие пригодность к работе в виде нейтронно-образующих мишеней на исследовательской ядерной установки «Источник Нейтронов». Показана степень взаимного проникновения слоёв твердофазного соединения Ta-W-Ta с прослойками Ti, обеспечивающая высокий уровень адгезии плакированных слоёв при использовании метода горячей вакуумной прокатки. Определены параметры деформации необходимые как для возникновения твердофазной связи, так и для образования надёжного твердофазного соединения слоёв тугоплавких металлов тантала и вольфрама через титановую прослойку, с прочностью соединения, превышающей значение менее прочного материала. Изучена возможность использования способа химического газофазного осаждения (ХГО) для покрытия боковых граней мишеней.